2007
DOI: 10.1016/s2173-5115(07)70360-3
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial needle aspiration of hilar and mediastinal lymph nodes

Abstract: Punção aspirativa transbrônquica por agulha de linfonodos hilares e mediastinais Transbronchial needle aspiration of hilar and mediastinal lymph nodes Recebido para publicação/received for publication: 06.07.04 Aceite para publicação/accepted for publication: 07.03.26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Also Cetinkaya et al [36] found that diagnosis was made by TBNA in 65% of tuberculosis patients and 100% of patients with carcinoma. Again, the present study agreed with Lannes et al [25] who stated that sarcoidosis can only be definitively diagnosed through the detection of non caseous granuloma and TBNA with a fine needle plays a limited role in the diagnosis of the disease. Using TBNA concomitantly with transbronchial biopsy or even bronchial biopsy improves diagnostic efficiency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also Cetinkaya et al [36] found that diagnosis was made by TBNA in 65% of tuberculosis patients and 100% of patients with carcinoma. Again, the present study agreed with Lannes et al [25] who stated that sarcoidosis can only be definitively diagnosed through the detection of non caseous granuloma and TBNA with a fine needle plays a limited role in the diagnosis of the disease. Using TBNA concomitantly with transbronchial biopsy or even bronchial biopsy improves diagnostic efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Also Lannes et al [25] observed enlargement of main carina in 59%, enlargement of secondary carina in 16%, right or left paratracheal bulging in 7%, bulging on the posterior trachea wall in 4%, bulging of the right or left main bronchus in 7% and 7% of cases showed no abnormalities. Also Matsuoka et al [26] stated that endobronchial nodules were found in 0-33% of sarcoidosis patients.…”
Section: Discussionmentioning
confidence: 92%
“… 32 , 33 In 2007, experts at INCA reported their experience with bronchoscopy-guided transbronchial needle aspiration, which is considered a safe and effective procedure. 34 Samples were deemed satisfactory in 57% of the cases, 81% of those allowing a definitive diagnosis. 34 Some groups have also developed expertise in CT-guided transthoracic fine-needle aspiration, showing high diagnostic yield, accuracy, and safety.…”
Section: Diagnostic Proceduresmentioning
confidence: 97%
“… 34 Samples were deemed satisfactory in 57% of the cases, 81% of those allowing a definitive diagnosis. 34 Some groups have also developed expertise in CT-guided transthoracic fine-needle aspiration, showing high diagnostic yield, accuracy, and safety. 35 After 2010, endobronchial ultrasound was introduced in a few large institutions, and the initial experience with 50 cases has been reported.…”
Section: Diagnostic Proceduresmentioning
confidence: 97%
“…1). 37 The primary role of lymphatics is to regulate interstitial fluid volume in conjunction with constantly changing volume and pressure in the blood vasculature. 38,39…”
Section: Human Lung Structure Function and Cellular Compositionmentioning
confidence: 99%